A Study of adsorption of crystal violet dye from water using biochar derived from olive tree (Sebha University Conference Proceedings, 2025)
Adsorption system is one of the most widely used chemical methods for removing dissolved pollutants from water, such as dyes. This system is characterized by its high efficiency and low cost, in addition high adsorption capacity of the adsorbent. In this study, local biochar derived from olive waste cake was used as an adsorbent for the removal of crystal violet from aqueous solutions. The adsorbent characterization study was performed using four-transform infrared (FTIR) spectroscopy and scanning electron microscopy (SEM). Some factors affecting the adsorption rate were evaluated, such as contact time, initial dye concentrations, amount of biochar, and pH. The remaining dye concentrations in the solution after adsorption were analyzed using an ultraviolet-visible (UV-visible) spectrophotometer. The results obtained indicate that the best adsorption conditions were achieved at a contact time of 60 min, an initial dye concentration of 50 mg/L, a charcoal content of 0.3 gl. The maximum adsorption capacity for dye removal by biochar was found to be 8.93 mg/g.